SINOPSIS DE LAS CORYSTOSPERMACEAE (CORYSTOSPERMALES, PTERIDOSPERMOPHYTA) DE ARGENTINA. I. HOJAS (Ameghiniana, 2013)
In the first part of this paper, the author gives general information on the morphology, organization and story of the Corystospermaceous foliage. In the subsequent chapters, the author offers a key of genera and the revision of Dicroidium, Johnstonia and Xylopteris, with a total of 12 species. Under each taxon, the synonymy, types, features, remarks, geo and stratigraphical distribution are given. Photographs and drawings of each species are also given.